The role of services and facilities in populity of rural settlements (case study: The villages in central region of Birjanation sustainabild city) - Hashemi, Hossein; Jafari, Hamid; Ahmadian, Mohammad Ali (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The studies show that today, the process of the social-economic changes and the increasing dynamism and replacement of the human groups have led to the changes in the rural areas. Therefore, the issue that basically, which factors have been effective on population sustainability in the rural settlements has been always arisen. The current study also has sought to find answer to this question. The current study is of descriptive-analytical type in terms of the methodology. The statistical population of the current study is all the villages in central zone of Birjand City which have had a population of more than 100 people (89 villages) according to 2016’s census. In order to determine the sample size, firstly 9 rural settlements in central zone of Birjand City which had the highest population decrease during 2006 to 2016, were selected. Then, based on the number of households in these 9 villages (691 households), 247 households were chosen according to Cochran Formula, to fill in the questionnaire, and finally, the samples were distributed by the stratified random sampling based on the ratio of each village’s household share. The descriptive-inferential method by the use of the SPSS was utilized for data analysis. The results indicated that the services and facilities have had a significant role in population sustainability of the rural settlements.